Adopting Contextual Teaching and Learning Model in Creative Writing - Donny Adiatmana Ginting; M. Zaim (The Seall Journal, 2023)
The aim is to implement the contextual teaching and learning (CTL) model increative writing classes for students in higher education. The background is thatstudents need help finding ideas, topics and themes relevant to their writing,especially in writing poetry and short story. The pre-experimental research is usedwith one group pre-test and post-test. The sample is thirty students, which usedsimple random sampling to select the sample. Assessment criteria for poetry and ashort story are used to check the quality of students' creative writing. Thequestionnaire is used to know students' perceptions of applying CTL in creativewriting. The author used t-tests and descriptive statistics as data analysis in thisresearch. The result showed that contextual teaching and learning influencedstudents' learning outcomes and motivation and improved the production of writingpoetry and short stories. Students believe that CTL helps them find the ideas, topicsand themes related to their daily life and experience in the creative writing class Keywords: Contextual Teaching and Learning, Creative Writing, Higher Education